Interaction of magnesium with potassium in sugarcane - Garcia, Ariani (2019)
The aim of this study was to evaluate the effect of Mg2+ and K+ concentrations, and Mg2+ foliar application on the root and shoot growth, as well as to check the alterations on the nutritional status and carbohydrates partitioning in sugarcane plants. For this purpose, three studies were conducted: i) evaluation of the effect of Mg2+ concentrations (adequate and deficient) on the sugarcane plants development; ii) metabolic and nutritional alterations in sugarcane due to Mg2+ imbalance caused by K+ high level; iii) efficiency of the Mg2+ foliar application in sugarcane plants grown under varied levels of K+ and Mg2+. The experiments were estabilished in greenhouse and the plants grown in nutrition solution. The evalutions were: leaf chlorophyll content, root morphological parameters (length and root diameter), dry matter production of plant parts, nutritional composition and starch, sucrose and reducing sugars partitioning in the different plant parts. In general, the adequate supply of Mg2+ resulted in higher dry matter production, sucrose concentration in the stalks and root/shoot ratio. Chlorophyll a, b and carotenoids were lower in Mg2+ deficient plants. Moreover, higher concentration of starch and soluble sugars were observed in the leaves and lower starch concentration in the stalks of these plants. Besides, Mg-deficient plants had shorter root length and larger diameter, which presented higher K+ concentrations in the root and higher translocation of this cation to the shoot. Increase in K+ concentration in the nutrition solution reduced Mg2+ concentration in the roots, young leaves, old leaves and stalks of sugarcane, even in Mg2+ control plants. Regardless Mg2+ nutrition, at the highest level of K+, all the plant growth parameters evaluated in this study were reduced. Plants grown under Mg2+ deficiency obtained higher starch concentration in the stalks at higher K+ level. Magnesium foliar application raised the sucrose concentration in the stalks and reduced the starch, regardless the K+ level evaluated. In addition, bigger plants were observed with foliar application and high K+ level, at both Mg2+ levels. For the plant growth parameters, with or without foliar application, Mg2+ deficiency seemed to greater affect the sugarcane plants than the high levels of K+.